Mapping The Needs Of Digital Information Services For Children With Special Needs - Masdah, Siti; Meilantika, Ayu Diana; Jiu, Cau Kim; Amelyadi, Amelyadi; Ariyanti, Sri (International Journal of Health Sciences, 2025)
Parents of children with Down syndrome face ongoing challenges in accessing relevant and trustworthy health information. With the increasing use of digital platforms, understanding parents’ needs and preferences is crucial for developing effective and inclusive digital health services. This study aims to map the digital health information needs of parents of children with Down syndrome, identify preferred information sources and digital platforms, and explore expectations regarding features of digital health applications. Methods use A descriptive quantitative study was conducted using a structured questionnaire distributed to parents of children with Down syndrome in Indonesia. Data were analyzed to assess patterns of digital information usage, platform preferences, and specific content and feature expectations. The results findings indicate that 83.6% of parents frequently seek digital health information, with WhatsApp groups (81.8%) and community networks like POTADS (80.0%) being the most accessed sources. Parents expressed a strong preference for digital tools that are free, user-friendly, and available in the local language. The most desired features in a health application include home-based therapy guidance (94.5%), educational videos (87.3%), parent forums (72.7%), and online consultation with healthcare professionals (67.3%). There is a high demand among parents for digital health platforms that offer accessible, relevant, and interactive content tailored to the needs of children with Down syndrome. Designing effective digital services requires collaboration across sectors and the integration of digital health literacy initiatives into existing family support systems to ensure equitable access and improved care outcomes.